(untitled) (Jurnal Pendidikan Fisika, 2019)
The research aimed to describe the Islamic based physics science learning model in the subject of measurement at Uminda Islamic School in Gowa by using a qualitative approach the result of research can be seen in implementation learning activities: Praying, read Al-quran and learning process. The students inspired the teaching of islam by instilling religions valves including knowing, understanding the living Gods creating with the Universe of the solar system, life on earth and also the implementation of religions extracurricular activities. The closing learning process, the teacher and the students made conclusion together Islamic based science learning model in physics lesson on the solar system and life on earth at Uminda Islamic School in Gowa with using with implementatively formulated model namely “Dialogical Diodik” with accordance with the study of Islamic based science physics learning model from the aspect of the of the interdisciplinary approach because it only involved two science and religions extracurricular activities through faith and piety learning. The students were given lesson to observe the universe event and mental spiritual formation which was integrated with the planting of religions valves, but there were still limited teacher resources to do it. Keywords: Model, Pembelajaran IPA, Fisika, berbasis, Islam. Penelitian bertujuan untuk menggambarkan Model pembelajaran IPA Fisika berbasis Islam pada Pokok Bahasan Pengukuran di MTS Uminda Kabupaten Gowa . dengan menggunakan pendekatan kualitatif. Hasil penelitian dapat terlihat pada implementasi langkah –langkah pembelajaran,mulai dari kegiatan pembelajaran pendahuluan :Membaca doa, membaca ayat suci Al Quran surat-surat pendek,kegiatan pembelajaran Inti :Menghayati ajaran agama Islam dengan menanamkan nilai-nilai agama diantaranya mengetahui, memahami dan menghayati ciptaan Tuhan dengan adanya alam semesta sistem tata surya dan kehidupan di bumi dan implementasi ektrakurikuler keagamaan.kegiatan pembelajaran Penutup .Guru dan peserta didik bersama-sama menyimpulkan Model pembelajaran IPA berbasis Islam pada pelajaran fisika pokok bahasan sistem tata surya dan kehidupan di bumi pada Madrasah Tsanawiyah Swasta Uminda Kabupaten Gowa menggunakan model yang dirumuskan secara implementatif yaitu model Diadik Dialogis yang sesuai dengan kajian model pembelajaran IPA-Fisika berbasis Islam dari aspek pendekatan interdisipliner karena hanya melibatkan dua disiplin ilmu IPA dan agama. Selanjutnya di integrasikan pada kegiatan ekstrakurikuler Keagamaan melalui pembelajaran iman dan taqwa peserta didik di berikan pembelajaran mengamati kejadian alam semesta dan pembinaan mental spiritual yang di integrasikan dengan penanaman nilai-nilai Agama. Namun masih terbatas sumber daya Guru untuk melaksnakan hal tersebut. Kata kunci: Pembelajaran IPA, Fisika, berbasis Islam.